2007
DOI: 10.48550/arxiv.0709.0319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Bohr radius relationship to spin-orbit interaction, spin magnitude, and Thomas precession

David C. Lush

Abstract: The dynamics of the spin-orbit interaction in atomic hydrogen are studied in a classical electrodynamics-like setting. A Rutherfordian atomic model is used assuming a circular electron orbit, without the quantum principle as imposed arbitrarily in the Bohr model, but with an ad hoc incorporation in the electron of intrinsic spin and associated magnetic dipole moment. Analyzing the motions of the electron spin and orbital angular momenta, it is found that in the presence of Thomas precession, the total angular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Since Thomas's analysis, little attention seems to have been paid to the problem of angular momentum conservation in semiclassical models of hydrogen-like atoms. Recently, however, Lush has revisited this problem and, using a different approach to ours, concluded that not even the orbit-averaged value of l + s is conserved in this problem [25,26]. Lush attributes the reason for the different finding in [2] to Thomas's omission of the contribution of hidden momentum to the force on a magnetic dipole and suggests the Thomas precession as the source of the nonconservation.…”
Section: Discussionmentioning
confidence: 79%
“…Since Thomas's analysis, little attention seems to have been paid to the problem of angular momentum conservation in semiclassical models of hydrogen-like atoms. Recently, however, Lush has revisited this problem and, using a different approach to ours, concluded that not even the orbit-averaged value of l + s is conserved in this problem [25,26]. Lush attributes the reason for the different finding in [2] to Thomas's omission of the contribution of hidden momentum to the force on a magnetic dipole and suggests the Thomas precession as the source of the nonconservation.…”
Section: Discussionmentioning
confidence: 79%
“…(Alternatively, the torque on the orbit could have been calculated in the electron rest frame based on the Biot-Savart force on the proton transiting the intrinsic magnetic field of the electron, obtaining the same result [23]. The torque must also be obtainable in the laboratory frame.…”
Section: Angular Momentum Nonconservation Due To the Thomas Precessionmentioning
confidence: 99%